Treatment Decision: Preference of Household Head Elderly Amid Source of Livelihood In Nepal - Bhusal, Durga (Butwal Campus Journal, 2021)
A burden considered elderly people in our work life-related society are in a situation that their potential is not sufficiently recognized for active management. Building and utilization of their abilities is an essential basis for the well-being of senior citizens. The aim of this study is to highlight and discuss the relation between treatment decision, and livelihood sectors of household headship of senior citizens and to explore their anticipation in the context of changing society of Nepal. 565 household head senior citizens as the respondents were taken into account to collect the information about independent and dependent variables. The study used reported source of livelihood as independent and preference to treatment decision as dependent variables based on the data of Nepal Social Inclusion Survey 2018. The study showed source of livelihood favoring traditional healer. Favoring the belief based rather than the facts treatment way is the challenge of society that should be considered seriously. Unprecedented but needy segment of development for the ultimate social and economic progress of Nepal is to modernize the society. However, household head senior citizens have not understood this as the needy matter of change being in a particular source of livelihood.